Healthy lifestyle factors and male perpetration of intimate partner violence: a cross-sectional study in Mwanza, Tanzania - Anna E. Jacob; Gerry Mshana; Neema Mosha; Ramadhan Hashim; Simon Sichalwe; Donati Malibwa; Saidi Kapiga; Philip Ayieko; Heidi Stöckl (Taylor & Francis Group, 2024)
Background In Tanzania, nearly half of ever-married women have experienced some form of intimate partner violence (IPV), yet little knowledge of IPV from the male perspective exists. Objective To explore the role of essential healthy lifestyle factors, diet, sleep, and exercise, and their potential role in IPV perpetration. Methods A cross-sectional survey was conducted with 1,002 young men (ages 18-24), 754 of which were in an intimate relationship in the previous year. The study took place in Mwanza, Tanzania and used multivariable logistic regression models to explore associations between male perpetration of IPV and diet, sleep, and exercise. Results Six types of IPV perpetration were investigated separately and the prevalence of controlling behaviours (79.4%), economic abuse (30.6%), emotional abuse (47.3%), physical violence (16.4%), sexual violence (23.3%), and combined physical and/or sexual violence (32.1%) were obtained. Regular exercise demonstrated a protective effect for economic abuse perpetration; the chance of mildly active individuals perpetrating economic abuse was 38% less than their inactive counterparts (p = 0.003). Associations with sleep were varied and did not show a clear directional relationship. Diet, defined as poor food variety, was positively associated with every IPV type except physical violence and was significant in sexual violence perpetration (aOR:1.57, 95%CI:1.21-2.05). Conclusions The results from this study indicate that considering healthy lifestyle behaviours - diet, sleep, and exercise - in the design of intervention programmes may be beneficial in reducing IPV perpetration in Tanzania, and that they should be considered alongside previously established evidence-based risk factors.